2002
DOI: 10.1006/dbio.2002.0680
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MEK or cdc2 Kinase Parthenogenetically Activates Mouse Eggs and Yields the Same Phenotypes as Mos−/− Parthenogenotes

Abstract: Mammalian eggs are arrested in metaphase II of meiosis until fertilization. Arrest is maintained by cytostatic factor (CSF) activity, which is dependent on the MOS-MEK-MAPK pathway. Inhibition of MEK1/2 with a specific inhibitor, U0126, parthenogenetically activated mouse eggs, producing phenotypes similar to Mos(-/-) parthenogenotes (premature, unequal cleavages and large polar bodies). U0126 inactivated MAPK in eggs within 1 h, in contrast to the 5 h required after fertilization, while the time course of MPF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
100
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 40 publications
12
100
0
Order By: Relevance
“…7A). Treatment of U0126, the specific MEK inhibitor, 24,25 caused disorganized spindles and GM130 dispersion into the cytoplasm in mouse oocytes.…”
Section: Sup Vid 6c)mentioning
confidence: 97%
“…7A). Treatment of U0126, the specific MEK inhibitor, 24,25 caused disorganized spindles and GM130 dispersion into the cytoplasm in mouse oocytes.…”
Section: Sup Vid 6c)mentioning
confidence: 97%
“…In addition, full-term embryonic development was achieved in mice and pigs by using TPEN as the only agent for oocyte activation. Moreover, different protein synthesis inhibitors such as puromycin (De Sutter et al 1992, Lu et al 2006) and cycloheximide (Moses & Kline 1995, Rogers et al 2006 have been shown to alleviate meiotic arrest by interrupting the continuous synthesis of cyclin B. Roscovitine, in turn, was shown to induce the meiotic release by direct inhibition of the cdk1 function (Phillips et al 2002).…”
Section: -Triggermentioning
confidence: 99%
“…CSF activity results from the activation of various pathways in which the APC/C inhibitor Emi2 plays a key role (Shoji et al, 2006;Tung et al, 2005). The Mos/MEK1/ERK1 and ERK2 MAP kinases cascade is also involved, but its exact mode of participation in the CSF activity remains not fully understood (Araki et al, 1996;Colledge et al, 1994;Hashimoto et al, 1994;Phillips et al, 2002;Sagata et al, 1989;Verlhac et al, 1996). Recent papers by T. A c c e p t e d M a n u s c r i p t downstream substrate of ERK2, in Xenopus oocytes is a key regulatory event in stimulating Emi2 activity (Inoue et al, 2007;Nishiyama et al 2007).…”
Section: Duration Of M-phase: the Affair Of Mpf Stabilitymentioning
confidence: 99%